Butyrylcholinesterase and 24 h-urinary copper excretion as compliance assessment in long-term treated Wilson’s disease - Hefter, Harald; Novak, Max; Rosenthal, Dietmar; Meuth, Sven G.; Luedde, Tom; Albrecht, Philipp; Hartmann, Christian J.; Samadzadeh, Sara (Frontiers in Neurology, 2025)
Background and aim of the studyCompliance is the most challenging aspect of long-term therapy in Wilson’s disease (WD). Evidence is presented that butyrylcholinesterase (CHE) can be used as a sensitive biomarker to detect compliance problems in long-term treated WD-patients.MethodsFor the present retrospective, monocentric study demographical and treatment related data of 108 WD-patients (who had been treated at the Clinic of Neurology of the university hospital in Düsseldorf (Germany) between 2/2005 and 1/2021) were extracted from the charts. These patients underwent 2003 therapy control visits. The present study focuses on the analysis of three parameters of copper metabolism (serum levels of ceruloplasmin (CER-S), copper (CU-S) and the 24 h-urinary copper excretion (24 h-UCU)) and the serum levels of CHE (CHE-S). A patient was classified to be non-compliant when in his charts at least 8 24 h-UCU-values were found, and all his 24 h-UCU-values were larger than 60 μg/d (N-COM8-group). A patient was classified to be compliant when at least one of at least 8 24 h-UCU-values was lower than or equal to 60 μg/d (COM8-group).ResultsCHE-S was significantly (p < 0.05) different between thus defined compliant or non-compliant patients. Neither CU-S nor CER-S nor calculated free (non-ceruloplasmin-bound) serum copper levels (NCC-S) were significantly different between the NCOM8- and COM8-group. Analysis of the area under the curve and sensitivity and specificity by means of ROC-curves underlined the sensitivity of CHE-S in contrast to the insensitivity of CU-S and CER-S to detect patients who had been classified as compliant/non-compliant on the basis of their 24 h-UCU-values.ConclusionWhen compliance of WD-patients is classified on the basis of their 24 h-urinary copper excretion CHE-S is more sensitive to detect problems of non-compliance than serum levels of copper, of non-ceruloplasmin bound free copper or ceruloplasmin. Therefore, CHE-S may be used as an easy to determine further biomarker for compliance assessment in long-term treatment of WD in addition to 24 h-UCU.